Pengaruh Pemberian Terapi Teknik Slow Deep Breathing Terhadap Tekanan Darah Pada Penderita Hipertensi di Wilayah Kerja Puskesmas Mokoditek Kec. Bolangitang Timur - Defitrianti Tampilang; Rahmat Hidayat Djalil; Zainar Kasim (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2023)
Hypertension is defined as a condition of systolic blood pressure ≥ 140 mmHg, and diastolic blood pressure ≥ 90 mmHg. Therapyslow deep breathing is a deep breathing exercise consisting of diaphragmatic breathing andPursed Lips. A breathing method with a breathing frequency of less than or equal to 10x/minute, with a long exhalation phase is able to reduce the blood pressure of hypertension sufferers. The aim of this research is to determine the effect of providing technical therapySlow Deep Breathing on blood pressure in hypertensive patients. This research method uses designQuasy-Experiment with a planOne group Pretest- Posttest Design, The sample in the research consisted of 15 respondents, the research instruments used were SOP and digital tension. The statistical test used was the dependent t-test. The research results obtained a value of p=0.000 (α ≤ 0.05) from the T-test while the Wilcoxon test obtained p=0.001 (α ≤ 0.05) meaning that there was an effect of providing technical therapySlow Deep Breathing on blood pressure of hypertension sufferers in the working area of ​​the Mokoditek District Health Center. East Bolangitang. There is an influence of providing technical therapySlow Deep Breathing on blood pressure of hypertension sufferers in the working area of ​​the Mokoditek District Health Center. East Bolangitang. It is recommended that it can be an appropriate and easy alternative treatment for lowering blood pressure in hypertension sufferers without requiring costs, it can be done anywhere and at any time.